APPLICATION AND BELIEF OF BREAST SELF-EXAMINATION (BSE) IN BREAST CANCER IN FEMALE STUDYING IN SCIENCE AND SOCIAL SCIENCES: THE CASE OF TURKEY - Seda SÖGÜT (Rojan GÜMÜŞ, 2020)
In Turkey, women, breast cancer is the most common type of cancer with 25%. Early diagnosis of breast cancer facilitates treatment and prolongs patient life. BSE which performed at regular intervals and accurately is a simple, economic method that protects the privacy of women in the early diagnosis of breast cancer. The aim of this study was to investigate the beliefs and practice of breast cancer and BSE in women studying outside the health field. Descriptive research was used to comment for the beliefs and practice of breast cancer and BSE in 600 women studying in science and social sciences of a University. Descriptive characteristics, breast cancer and breast self-examination were used to collect data and the Champion Health Belief Model Scale (CHBMS) was used. The difference between the mean CSIMS scores of students with and without BSE was evaluated statistically.The participants was found that 15.2% (n = 91) of students applied BSE regularly every month. 17.5% of participants indicated not be a sign of breast cancer. In the early diagnosis of breast cancer, 54% of participants were indicated can used BSE. Moreover, 49.8% of the participants noted that they did not get any information about BSE before. The difference between participants who applied and did not apply BSE was statistically significant the total scale means (P=0.007). It was concluded that female students studying in science and social sciences had insufficient knowledge about breast cancer and BSE early diagnosis, symptoms, and physician examination.Peer education programs are recommended. Keywords :Student, breast cancer, breast self examination (BSE), health, beliefs.